2020
DOI: 10.1177/2158244019899104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trust on Customer Engagement: Empirical Evidence From the Insurance Industry in Ghana

Abstract: This study examined the influence of trust dimensions on customer engagement, and the resultant impact of customer engagement on customer loyalty in the context of life insurance. Furthermore, it investigated the mediating role of customer engagement in the relationships between trust dimensions and customer loyalty. A total of 452 valid responses from life insurance customers in Ghana were examined using structural equation modeling (SEM). The results revealed that trust in service provider, trust in the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 130 publications
1
37
0
4
Order By: Relevance
“…Likewise, it is gradually being viewed as a capable driver of future firm performance (Harrigan et al, 2018;Hollebeek, 2012;Loureiro & Lopes, 2019;Rather, 2020). Several studies have confirmed the promising benefits of engaged customers, demonstrating these can show improved customer loyalty, trust, emotional ties, commitment, customer identification, customer experience, customer participation, and so on (Agyei et al, 2020;Brodie et al, 2013;Carvalho & Fernandes, 2018;Kaur et al, 2020;Prentice et al, 2019;Rather, 2020;Rather et al, 2019a;Solem, 2016). These can be critical to the realization of higher firm performance results such as growth in sales, brand referrals, enriched cocreative experiences, and superior profitability (Hollebeek et al, 2014;Loureiro & Lopes, 2019).…”
Section: Customer Engagementmentioning
confidence: 99%
“…Likewise, it is gradually being viewed as a capable driver of future firm performance (Harrigan et al, 2018;Hollebeek, 2012;Loureiro & Lopes, 2019;Rather, 2020). Several studies have confirmed the promising benefits of engaged customers, demonstrating these can show improved customer loyalty, trust, emotional ties, commitment, customer identification, customer experience, customer participation, and so on (Agyei et al, 2020;Brodie et al, 2013;Carvalho & Fernandes, 2018;Kaur et al, 2020;Prentice et al, 2019;Rather, 2020;Rather et al, 2019a;Solem, 2016). These can be critical to the realization of higher firm performance results such as growth in sales, brand referrals, enriched cocreative experiences, and superior profitability (Hollebeek et al, 2014;Loureiro & Lopes, 2019).…”
Section: Customer Engagementmentioning
confidence: 99%
“…Al Abdulrazak and Gbadamosi (2017) also mentioned that trust was a crucial factor in building relationships with clients. It is defined as an individual’s belief in the credibility of others that can be determined by their competence, integrity, and benevolence (Agyei et al, 2020; Xie & Peng, 2009). According to Brown et al (2019), a relationship is established when both parties trust each other.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Kalaiarasi and Mugunthan (2020) Proper communication channel in an organization required for successful CRM and more focus should give to solve top-level strategic management issues. Agyei et al (2020) Trust was a factor which profoundly affects customer engagement and customer loyalty. Xing and Devasia (2020) If an insurance company in Kuala Lumpur had customer-oriented strategies, then the rate of customer retention was high.…”
Section: Classification By Country-wise (Where the Research Was Done)mentioning
confidence: 99%